Depletion of the RNA binding protein QKI and circular RNA dysregulation in T-cell acute lymphoblastic leukemia - Alessia Buratin; Bruno Palhais; Enrico Gaffo; Juliette Roels; Julie Morscio; Jolien Van Laere; Silvia Orsi; Geertruij te Kronnie; Pieter Van Vlierberghe; Panagiotis Ntziachristos; Stefania Bortoluzzi (Haematologica)
Not available.